The Abuse of Children Growing Up in Conflicting Families - Susanu, Neaga (New Trends in Psychology, 2022)
Children must be respected as separate beings. Their privacy, personal life and normal development must be respected. Children’s rights to protection and liberty must be recognized and a safe environment for the life or development of children must be guaranteed when they are abused or exploited. From a humanitarian and legal perspective, the social need to care for children and protect them from unfavorable and sometimes dangerous family environments is relatively recent. Unresolved conflicts between husband and wife affect children because they have endless love and loyalty to their parents. Conflicts can occur in any couple, but unresolved ones create serious problems. Child abuse has been a public debate since the 1960’s. Today, however, killing children, forcing minors to work long hours, or treating minors as “young adults” is considered abusive behavior, but in the past, it was common practice. Children who are abused or abused at home change their social behavior.